Organizational Justice and Job Satisfaction among Malaysian Workers - Mazidah Mohd Dagang, Azlina Abu Bakar, R Zirwatul Aida R Ibrahim, Jumadil Saputra, Siti Nazilah Mat Ali, (Opción, 2019)
The aim of the study is to investigate the organizational justice and job satisfaction among Malaysian workers via hierarchical multiple regression as a method. The result indicated that organizational justice, job control and social support uniquely predict wellbeing (job satisfaction). Interestingly, the pattern of interaction showed that employees who perceived the interactive effect of high interactional justice and high job control reported lower levels of job satisfaction. In conclusion, it is important to promote a just and inclusive organizational working culture which can create a sense of belonging, satisfaction and commitment among employees